Analisis peran kredit perbankan dalam pendanaan usaha mikro, kecil, dan menengah (UMKM) serta hubungannya dengan pertumbuhan ekonomi di Provinsi Jambi - Anggraini, Dessy; Haryadi, Haryadi (Jurnal Paradigma Ekonomika, 2020)
This research aims to: (1) analyze the development of micro, small, and medium enterprise credit in Jambi Province, (2) analyze the factors affecting micro, small, and medium enterprise credit in Jambi Province by using regression panel data, (3) analyze relationship of micro, small, and medium enterprise credit with economic growth in Jambi Province using Pearson correlation. The result of the equation estimation panel data test using the REM model showing that real interest rate, per capita income, and the number of business units simultaneously have a significant effect on micro, small, and medium enterprise credit with a value of F significance statistic equal to 88,82. The result of partial estimation obtained a rill interest rate has a significant effect on micro, small, and medium enterprise credit. While per capita income and numbers of business units variable have no significant effect on micro, small, and medium enterprise credit because of a significance value of t statistic equal to 0,662959 and -0,259486. The Pearson correlation result showing the relationship micro, small, and medium enterprise credit to economic growth in Jambi province is very strong in a positive direction.